Detection of Brucella spp. in artisan cheese commercialized in Parnaíba, Piauí state, Brazil - Bezerra, Suely Santos; Kim, Pomy de Cássia Peixoto; Santos, Francisco José de Seixas; Castro, Karina Neoob de Carvalho; Lira, Nair Silva Cavalcanti; Mendes, Emiko Shinozaki (Medicina Veterinária, 2019)
The aim of this study was to detect Brucella spp. in artisanal cheese commercialized in Parnaíba city, Piauí state, Brazil. For this study, 30 samples of curd cheese (500g) were randomly collected from different points in the commercialization process. In the laboratory, 25g aliquots of the samples were suspended in Brucella broth; after this procedure, 10µL aliquots of this suspension were sown in Thayer Martin agar plates that were supplemented with 10% defibrinated sheep blood and VCNT antimicrobials. After inoculation, the samples were incubated at 37°C in microaerophilic conditions for 14 days. The suspected morphological colonies were identified and confirmed by polymerase chain reaction (PCR). From thirty samples of microbiologically analyzed cheeses, six samples (20%) were confirmed by PCR as bacteria from the Brucella genus. The detection of Brucella spp. was confirmed in cheese commercialized in markets or a public square (3.33%), bakery (3.33%) and small market (13.33%). Brucella spp. was detected in artisanal cheese commercialized in different points from Parnaíba city. Guidelines for the establishment of good practices for the production of artisanal cheese should be determined by the competent authorities. However, for the better control of human brucellosis it is necessary to control or eradicate bovine brucellosis in the herds.